THE EFFECT OF PROBLEM BASED LEARNING MODEL IN 2013 CURRICULUM ON LEARNING OUTCOMES AND SKILLS IN VOCATIONAL EDUCATION - Wagino Wagino; Nizwardi Jalinus; Rijal Abdullah; Ridwan Ridwan; Iffarial Nanda; Hariyadi Hariyadi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
This study aims to determine the effect of the problem based learning model on learning outcomes and skills in Motorcycle Engineering courses for D3 Automotive Engineering students, Faculty of Engineering, Padang State University. The research method used is an experiment with a modified pretest-posttest group research design. The sampling technique used is cluster random sampling, with Group 1 as the experimental class and Group 2 as the control class. The analytical technique used is the average difference test, analysis of the influence between variables, and determination of the coefficient of determination. The results of the study obtained that the average learning outcomes and motorcycle engineering skills in the experimental class was 89.56 while the control class was 81.54. The analysis of the influence between variables resulted in a biserial coefficient of 0.59 for learning outcomes and 0.44 for Motorcycle Engineering skills. The calculation of the coefficient of determination shows that the application of the problem based learning model contributes 35.00% to learning outcomes and 19.34% to Motorcycle Engineering skills. The relationship between Motorcycle Engineering skills and learning outcomes in problem based learning model learning is 31.69%. Based on the results of the study, it can be concluded that the application of the problem based learning model affects the learning outcomes and skills of Motorcycle Engineering students of D3 Automotive Engineering, Faculty of Engineering, Padang State University on CVT Maintenance material.Keywords: learning outcomes, Motorcycle Engineering skills, problem based learning